Implementasi Manajemen Hiperglikemi Pada Pasien Diabetes Melitus Tipe 2 Dengan Masalah Ketidakstabilan Kadar Glukosa Darah - Devi Mediarti; Syokumawena Syokumawena; Jihan Salsabila Rahmawati (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2026)
Background: Diabetes mellitus is a chronic disease characterized by blood glucose levels exceeding normal values over a long period. The term blood glucose is often referred to by the public as blood sugar. According to data from the South Sumatra Provincial Health Office, diabetes mellitus has been the most prevalent disease for three consecutive years, from 2020 to 2022. In 2020, there were 172,044 cases of diabetes, which increased to 279,345 cases in 2021. The signs and symptoms that can be found in patients with type 2 DM include polyuria (frequent urination), polydipsia (often feeling thirsty), polyphagia (frequent eating), and unexplained weight loss. To address this issue, nursing interventions are carried out with the aim of managing the risk of blood glucose instability. After three visits, it is hoped that the patient's blood glucose levels can stabilize through appropriate interventions, namely hyperglycemia management. Methods: In this case study, a case study design with a descriptive method is used. The approach used is the nursing care approach. The case study subjects consist of 2 patients with type 2 diabetes mellitus. The first patient is 67 years old and the second patient is 46 years old, both having the same nursing problems. This case study was conducted in the inpatient room of Ahmad Dahlan Hospital Muhammadiyah Palembang. Data collection techniques were through observation, interviews, and filling out case study instruments over 3 days in the care room. Result: After the implementation for 3 days, both subjects experienced a decrease in glucose levels with criteria showing a reduction through the management of hyperglycemia. Conclusion: This indicates that monitoring blood glucose levels in patients with diabetes mellitus is essential in order to know their glucose levels and help them maintain proper control.